Characterization of hierarchical porous materials - Mohd Abid, Mohd Asyadi Azam; Safie, Nur Ezyanie; Abdul Aziz, Mohd Fareezuan (Springer, 2022)
A pivotal function to verify the synthesis material is to comprehend the hierarchically porous material through the material characterization. This chapter discusses the vital characterization, especially for the as-prepared hierarchically porous materials, for further analyzing and understanding their behavior and properties. X-ray diffraction (XRD) is the most powerful technique in examining the crystallographic structure of a material. Chemical compounds can be identified using diffraction techniques based on their crystalline form. On the other hand, scanning electron microscope (SEM) analysis is essential for examining the hierarchically porous material’s microstructure and surface morphology. Besides, the approach which indicates and discloses the porous structure of the materials is characterized by the transmission electron microscope (TEM). The measurement determining and resulting in particular surface area of the materials are often preferred using Brunauer–Emmett–Teller (BET) characterization.